Assessing the polarization of a quantum field from stokes fluctuations - Klimov, A. B.; Bjoerk, G.; Soederholm, J.; Madsen, L. S.; Lassen, M.; Andersen, U. L.; Heersink, J.; Dong, Ruifang; Marquardt, Christoph; Leuchs, Gerd; Sanchez-Soto, L. L. (Physical Review Letters, 2010)
We propose an operational degree of polarization in terms of the variance of the Stokes vector minimized over all the directions of the Poincaré sphere. We examine the properties of this second-order definition and carry out its experimental determination. Quantum states with the same standard (first-order) degree of polarization are correctly discriminated by this new measure. We argue that a comprehensive quantum characterization of polarization properties requires a whole hierarchy of higher-order degrees. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05